The existence of values and norms in fishing community of Bontosua Island, Pangkep Regency - Sakaria, Sakaria; Sabiq, Muhammad; Arisnawawi, Arisnawawi (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2024)
This research tries to describe the existence of values and norms in the fishing community of Mattiro Bone Village. This research was conducted on Bontosua Pangkep Island. This research is a mix method. Data and information were obtained through in-depth interviews and limited observations from five informants determined by snowball sampling. The questionnaire was also distributed to 15 respondents. The data was then analyzed qualitatively to explain research data and facts. The existence of fishing communities is measured by the social capital they possess in the form of values and norms. The research results show that the existence of the values and norms of the fishing community on Bontosua Island is a community that is open or accepting of the values and norms that enter their community. The people of Bontosua still adhere closely to the values and norms that exist in their area, this is proven by several attached data such as a high level of mutual respect and a high level of mutual assistance. The research results also show that the community still accepts the arrival of outside parties, in this case the government and outside communities, if their aims and objectives are good for the fishing community on Bontosua Island.